2003
DOI: 10.1046/j.1365-2214.2003.00332.x
|View full text |Cite
|
Sign up to set email alerts
|

When adolescents disagree with their mothers: CBCL‐YSR discrepancies related to maternal depression and adolescent self‐esteem

Abstract: Subjective, psychological variables such as mothers' level of depression and self-esteem of adolescents may be useful to consider when interpreting informant discrepancy concerning the mental problems of adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
113
0
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(126 citation statements)
references
References 35 publications
9
113
0
4
Order By: Relevance
“…These findings are consistent with previous studies comparing parent reports and youth self-reports of adolescent emotional and behavioral problems [5,12,23,43]. In line with existing research, the level of parent-adolescent concordance was higher for the externalizing scale than for the internalizing scale [8,34]. This could be due to the fact that internalizing problems are less observable.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings are consistent with previous studies comparing parent reports and youth self-reports of adolescent emotional and behavioral problems [5,12,23,43]. In line with existing research, the level of parent-adolescent concordance was higher for the externalizing scale than for the internalizing scale [8,34]. This could be due to the fact that internalizing problems are less observable.…”
Section: Discussionsupporting
confidence: 92%
“…In general, previous studies revealed a higher parent-child agreement regarding externalizing symptoms compared to internalizing symptoms [8,34]. It has been argued that externalizing problems are more openly observable and directed at others.…”
Section: Introductionmentioning
confidence: 88%
“…These authors observed that overall agreement between children and parent reports was low to moderate, whereas parent-child agreement in a sample of enuretic children was moderate to good (15). Despite -ence the severity of reported problems, clinical work of including multiple informants in the diagnostic evaluation of children and adolescents (16). Apparently when parents evaluate their children, more externalizing problems are reported, while children, on self-report, point out more internalizing problems.…”
Section: Introductionmentioning
confidence: 93%
“…Apparently when parents evaluate their children, more externalizing problems are reported, while children, on self-report, point out more internalizing problems. Even though there is consensus that is important to have multiple informants during child/adolescents' assessment, the literature still has not reached a consensus on how to interpret the differences found in both reports (16).…”
Section: Introductionmentioning
confidence: 99%
“…ängst-lich gebundene Kinder die höchste Rate an hypochondrischen Gedanken und funktionellen Störungen haben [39]. Auch Studien zum Selbstbild in Abhän-gigkeit von einer depressiven Mutter weisen deutlich auf psychodynamische Verstehensansätze hin: In der Untersuchung einer norwegischen Arbeitsgruppe [40] …”
Section: » Bindungstheoretische Aspekte Werden Zur Erklärung Der Kds unclassified